2005
DOI: 10.1108/02683940510579777
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the general decision making style questionnaire in two UK samples

Abstract: Purpose - To examine the psychometric properties and construct validity of the general decision making style (GDMS) questionnaire in two UK samples. Design/methodology/approach - The GDMS takes the form of a self-report questionnaire which identifies five decision making styles: Rational, intuitive, dependent, avoidant, and spontaneous. It was administered to samples of business studies undergraduates in two UK business schools. Analyses included scale reliabilities, test-re-test reliability, and both explorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
127
5
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(150 citation statements)
references
References 20 publications
16
127
5
2
Order By: Relevance
“…Personal characteristics and individual differences affect general decision-making processes (Aminoff et al, 2012;Bazerman & Moore, 2013;Spicer & Sadler-Smith, 2005). As previously said, career decision-making processes are not only affected by one's educational background but also by role models (Flouri & Buchanan, 2002;Van Auken et al, 2006), self efficacy (Bandura, 1977;Bullock-Yowell, Andrews, & Buzzetta, 2011;Luzzo, 1993), and individual characteristics (Kidd, 1984;Law, 1981).…”
Section: Individual Characteristics and The Decision To Work For A Stmentioning
confidence: 91%
“…Personal characteristics and individual differences affect general decision-making processes (Aminoff et al, 2012;Bazerman & Moore, 2013;Spicer & Sadler-Smith, 2005). As previously said, career decision-making processes are not only affected by one's educational background but also by role models (Flouri & Buchanan, 2002;Van Auken et al, 2006), self efficacy (Bandura, 1977;Bullock-Yowell, Andrews, & Buzzetta, 2011;Luzzo, 1993), and individual characteristics (Kidd, 1984;Law, 1981).…”
Section: Individual Characteristics and The Decision To Work For A Stmentioning
confidence: 91%
“…For instance, an individual characterized by a spontaneous decision-making style is inclined to make impulsive and "instant" decisions. Their desire to get through the decision-making process as quickly as possible (Spicer and Sadler-Smith, 2005) may jeopardize the quality of the decisions made. In order to lessen an impact of the human factor, a marketing information system should be constructed to eliminate the individual differences of decision-makers in terms of their decision-making styles.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we can posit that individuals that fit under spontaneous decision-making style better handle marketing circumstances that require speedy decisions. Individuals in this style are characterized by a feeling of immediacy and the desire to get through the decisionmaking process as quickly as possible (Spicer and Sadler-Smith, 2005). Prior studies on decision speed view prompt action as a decisive competitive weapon for market innovation.…”
Section: Spontaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of cognitive styles has become evident not only in relation to political judgment, as investigations have shown that the ways in which we perceive information and derive meaning from it are also relevant for decision-making, problem-solving, learning, creativity, and the support of different values (Hayes and Allinson 1998;Kirton 1976;Spicer and Sadler-Smith 2005;Puccio et al 1995;Tetlock 2000;Van Den Broeck et al 2003). …”
Section: Introductionmentioning
confidence: 99%